2021
DOI: 10.3390/s21238139
|View full text |Cite
|
Sign up to set email alerts
|

Medical Range Radiation Dosimeter Based on Polymer-Embedded Fiber Bragg Gratings

Abstract: Fiber Bragg gratings (FBGs) are valuable dosimeters for doses up to 100 kilograys (kGy), but have hardly been used for the low-dose range of a few grays (Gy) required in medical radiation dosimetry. We report that embedding a doped silica fiber FBG in a polymer material allows a minimum detectable dose of 0.3 Gy for γ-radiation. Comparing the detector response for different doped silica fibers with various core doping, we obtain an independent response, in opposition to what is reported for high-dose range. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…For a polymer-embedded FBGs dosimeter, we previously showed good accordance for BWS ( ) due to low-dose radiation response ( D ) between experimental data and theoretical model [ 21 ]: in which is the Bragg peak wavelength, is the photo-elastic coefficient, and are the coefficient of thermal expansion for the coating and for the fiber, and are the coating and the fiber cross-sectional areas and , are Young’s modulus of the coating and of the fiber, and are respectively the coating and fiber mass heat capacity, and is the thermo-optic coefficient. If we consider ambient temperature variation ( ) and set for convenience, the total BWS can be expressed as follows: …”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…For a polymer-embedded FBGs dosimeter, we previously showed good accordance for BWS ( ) due to low-dose radiation response ( D ) between experimental data and theoretical model [ 21 ]: in which is the Bragg peak wavelength, is the photo-elastic coefficient, and are the coefficient of thermal expansion for the coating and for the fiber, and are the coating and the fiber cross-sectional areas and , are Young’s modulus of the coating and of the fiber, and are respectively the coating and fiber mass heat capacity, and is the thermo-optic coefficient. If we consider ambient temperature variation ( ) and set for convenience, the total BWS can be expressed as follows: …”
Section: Methodsmentioning
confidence: 97%
“…For this technique, the temperature coefficient ratio ( ) is 1.52, and the dose coefficient ratio ( ) is 1.18, which are different from one another as required. All theoretical coefficients are calculated with the constants presented in [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As with the coating, the embedding or packaging of the grating can also change its radiation sensitivity; an example of this is reported in [ 105 ]. Moreover, Lebel-Cormier et al recently reported a radiation dosimeter based on polymer-embedded FBGs [ 110 ]: they showed that, by gluing the FBG inside a square prism in different polymer materials and reducing the error in the peak detection to 0.03 pm, the induced shift depends linearly on the dose, up to 20 Gy, with a slope of about ~0.06 pm/Gy, which depends on the material choice and not on the fiber composition.…”
Section: Radiation Effects On Fbgsmentioning
confidence: 99%